ChemInform Abstract: Controllable Mono‐/Dialkenylation of Benzyl Thioethers Through Rh‐Catalyzed Aryl C—H Activation. Issue 4 (28th January 2014) - Zhang, Xi‐Sha; Zhu, Qi‐Lei; Zhang, Yun‐Fei; Li, Yan‐Bang; Shi, Zhang‐Jie
Abstract A thioether‐directed Rh‐catalyzed oxidative alkenylation of arenes is described.